Implementation of E-Learning Based Learning at Islamic University of Nusantara (UNINUS): The Implementation of E-Learning Based Learning at Nusantara Islamic University (UNINUS) - Aisyah, Ia Siti; Komarudin, Komarudin (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
The implementation of E-learning in Islamic higher education institutions presents unique challenges that require thorough investigation. This study explores the implementation of E-learning at Universitas Islam Nusantara (UNINUS) Bandung, focusing on its effectiveness, challenges, and integration with Islamic educational values. Employing a descriptive qualitative approach, data were gathered through interviews, classroom observations, and document analysis. The findings reveal that UNINUS has successfully implemented an E-learning model, positively impacting student academic quality and administrative efficiency. Three key factors contribute to its success: the development of comprehensive digital infrastructure, digital competency training for educators and students, and the integration of Islamic values in digital learning. However, challenges persist, such as improving the reliability of technical infrastructure and addressing varying levels of digital literacy among faculty and students. Additionally, resistance from some lecturers, due to limited technological skills and the need for further training, remains a significant obstacle. This study enriches the discourse on digital transformation in Islamic higher education and offers practical insights for other Islamic institutions aiming to adopt E-learning systems. It concludes that the successful implementation of E-learning in Islamic educational institutions requires a balanced approach that preserves traditional values while embracing technological advancements to enhance learning quality.